Census of the mountain gorilla Gorilla beringei beringei population in Bwindi Impenetrable National Park, Uganda - McNeilage, Alastair; Robbins, Martha M.; Gray, Maryke; Olupot, William; Babaasa, Dennis; Bitariho, Robert; Kasangaki, Aventino; Rainer, Helga; Asuma, Steven; Mugiri, Ghad; Baker, Julia (Oryx, 2006)
Mountain gorillas Gorilla beringei beringei are Critically Endangered, with just two small populations: in Bwindi Impenetrable National Park in south-western Uganda and the nearby Virunga Volcanoes on the borders with Rwanda and Uganda. A survey of the Bwindi population was carried out in 2002 and results were compared with the previous census in 1997. Our estimate of total population size increased over that period by c. 7% to 320 individuals and the structure and distribution of the population were largely unchanged. Signs of human disturbance were more common in 2002 than 1997, and gorillas tended to be found in areas of relative low disturbance. This suggested that disturbance could be a constraint on population growth and distribution but demographic stochasticity may also be responsible for the observed level of population change over a short time period. Other potential limiting factors, including habitat availability and disease, are discussed. While conservation activities in Bwindi have probably contributed to the stability of the population, strengthening of law enforcement and continued vigilance are needed to ensure the population’s long-term growth and survival
Keywords: Bwindi Impenetrable National Park; Gorilla beringei beringei; human disturbance; mountain gorilla; population census; Uganda.